Suffering & Sovereignty: Recent Canadian Jewish Interest in Indigenous People and Issues - Koffman, David S. (Canadian Jewish Studies / Études juives canadiennes, 2017)
This essay analyzes ways that Canadians Jews have been engaging with Indigenous people and issues since the turn of the millennium. It argues that communal Jewish interest in Indigenous issues developed in the wake of the Ahenakew affair in 2002, and then grew in breadth and depth after the launch of Canada’s Truth and Reconciliation Commission in 2008. The expansion of Jewish engagement in Indigenous matters bespeaks newfound mobilizations by Canadian Jews in the identity politics of ethnic/religious coalition building, toward multiple and sometimes competing ends, two of which are particularly salient: suffering and sovereignty. While the sufferings of the Jewish people and Indigenous peoples have been inexactly mapped onto one another, the attachments that many Canadian Jews have to the legacies of oppression, resistance, and recovery have profoundly shaped their eagerness to contemplate and engage Indigenous issues in particularly Jewish ways. Jewish engagements with First Nations also focus on the idea of “indigeneity” for the rhetorical power it may provide in debates about Israel as a colonial, post-colonial, or anti-colonial state. Canadian Jews to champion liberal support of First Nations, Jewish conversations around Indigenous suffering, heritage honour, and reconciliation have also foregrounded a set of tense questions about the extent to which Canadian Jews are and have been implicated in colonialism writ large, and about how Canadian Jews can or should best respond to its legacies. The two themes, suffering and sovereignty, are intertwined in a dynamic and unresolved tension, with one theme (suffering) inherently grappling with powerlessness, and the other (sovereignty), inherently grappling with power.